Do on-line labor market intermediaries matter? The impact of AlmaLaurea on the university-to-work transition - Manuel F. Bagues; Mauro Sylos Labini (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2007)
This paper evaluates the impact of the availability of electronic labor markets on university-to-work transition. In particular, we analyze the effect of the intermediation activity carried on by the interuniversity consortium AlmaLaurea on graduates' labor market outcomes. Different timing of universities' enrolment in AlmaLaurea produces counterfactuals that allow us to overcome the problems faced by previous empirical investigations. The evaluation is performed applying the difference-in-differences method to a repeated cross section data set. It is shown that, if the usual assumption concerning parallel outcomes holds, AlmaLaurea reduces individual unemployment probability and improves matching quality. Interestingly, it is also found that on-line intermediaries foster graduates' geographical mobility.
Keywords: J64; J68; G14; 330; Labor Markets Intermediaries; Job Search; Electronic Markets; Arbeitsvermittlung; Internetbasierter Dienst; Akademiker; Italien; Arbeitsmarktintegration